(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid advancement of quantum computing poses a serious threat to traditional cryptographic systems such as RSA and Elliptic Curve Cryptography (ECC), which rely on computational difficulty for security. Quantum algorithms like Shor’s and Grover’s have the potential to break or weaken these methods, putting modern communication systems at risk. To address this challenge, this work presents a quantum-safe com-munication framework that combines the BB84 Quantum Key Distribution (QKD) protocol with Post-Quantum Cryptography (PQC) techniques, aiming to ensure secure data exchange in the presence of quantum-capable adversaries. In this system, the BB84 protocol is simulated to enable secure key exchange between two parties over a virtual quantum channel. The generated key is refined through processes such as basis matching, error correction, and privacy amplification using SHA-256 to ensure reliability and secrecy. For secur-ing communication, One-Time Pad (OTP) encryption is used alongside HMAC-SHA3-256 to provide both confidentiality and message integrity. Additionally, file encryption is handled using the XChaCha20-Poly1305 algorithm, selected for its efficiency and strong protection against potential vulnerabilities like nonce reuse. To further enhance security, the framework integrates a hybrid key management approach using the Kyber-512 Key Encapsulation Mechanism (KEM) combined with a Key Deriva-tion Function (KDF), merging classical and quantum-resistant techniques. Experimental results demonstrate the effectiveness of the system, achieving a Quantum Bit Error Rate (QBER) of 2.5% and successful performance in both message and file en-cryption. Overall, this work contributes toward the development of practical and resilient communication systems designed for the emerging quantum era.